(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the origin of euphemism as a linguistic device in world linguistics, the history of its study, and the contributions of Uzbek, Russian, and European linguists to this field. It examines the use of euphemisms in social contexts, their stylistic and methodological features, and emphasizes both the positive aspects of euphemistic expression—such as politeness and sensitivity—and the negative ones, such as obscuring or abstracting the true meaning of speech. The article analyzes E.A. Agayan’s view of euphemism as a multifaceted ethnic phenomenon and O.N. Turbachev’s studies on euphemisms within specific mentalities and their relation to hunting terminology in the speech of people from Sweden, Finland, and Estonia. It also discusses the research of S. Otayev on Turkmen euphemisms, G.G. Musaboyev on Kazakh euphemisms, V.P. Darbakova on Mongolian euphemisms, and N.G. Mikhailovskaya’s work on euphemisms in the languages of Far Eastern peoples such as Chukchi, Khanty-Mansi, and Nanai. The article provides a comprehensive overview of the historical development and cultural significance of euphemisms.